Cockatoo Island stage 3: seawall failure and remediation - Wong, PK; Petropulos, P (Slope Stability 2013: Proceedings of the 2013 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2013)
The hematite mining operation at Cockatoo Island, Western Australia, required the construction of a 13 m high, composite earth and rockfill seawall to exclude 10 m tides from the Indian Ocean. The Stage 3 seawall is underlain by up to 30 m of soft, low permeability coralline sediments which are in turn underlain by stronger and higher permeability marine sediments and hematite scree layers. During initial construction, a 140 m section of the seawall failed when a height of 8.7 m was reached. This paper describes the post failure investigation and analysis results, and the remedial works which were successfully completed. The investigation results indicated the basal drainage characteristics of the coralline sediments to be variable along the length of the seawall. At the location of the failure, basal drainage was very low and this was considered to be a major contributing factor to the failure coupled with rapid construction of the embankment. Instrumentation and monitoring prior to the failure was limited, partly due to difficulties associated with high tidal fluctuations. In contrast, the remedial work was carried out successfully with a significantly improved instrumentation and monitoring system, including inclinometers, extensometers, piezometers, settlement plates, survey prisms and total pressure cells. A rigorous review and approval process was developed in conjunction with the client, Cockatoo Mining, using an observational method to assess the risk of instability prior to placing each additional embankment layer. The degree of client involvement and the collaborative approach adopted in relation to the observational method, approvals, data transfer, and joint management for the remedial work is extremely rare on most mines. The successful completion of the remedial work demonstrated that such a collaborative approach is a key ingredient to the successful completion of high risk projects in complex ground conditions.